Fragility or Frailty? The Stories of Five Women’s Transition to Old Age - Bramanti, Donatella; Nanetti, Sara (Italian Sociological Review, 2022)
This contribution aims to explore some of the major changes occurring in women’s transition to frailty during ageing, through the data from a qualitative survey and the lens of intergenerational relationships. As prominent figures in family care and supportive relationships, women will be observed from an intergenerational dialogue perspective, which allows to recognize the needs and potential of a supportive relationship. By analysing five real-life stories through dyadic interviews between five elderly women and their respective reference person, we seek to stimulate discussion on the protective and empowerment factors arising from family relationships, and on the risk factors, hindering this transition. The outcome is a multidimensional view of frailty, which distinguishes between ‘fragility’ and ‘frailty’ and includes both risk and resource factors.